SALES PROSES DALAM MENGINDENTIFIKASI, MEMAHAMI DAN MEMBUAT PRIORITAS BAGI NASABAH SEGMEN SMALL MEDIUM ENTERPRISE (SME) - Supendi, Muclis (MABIS, 2012)
Bank Customers have become more critical in choosing banks to transact with, in line with the increasing needs of their businesses. On the other side, Banks are faced with a more intense competition. In managing the banking sector, then the role of a bankâs staff in indentifying, understanding and prioritizing the segment to be served is of significant issue in contributing to the growth of the banking business. In the effort of retaining and to continuously increase the growth of lending and funding outstanding as well as the number of customers, the company is faced with constraints in the form of decreasing lending and funding outstanding from day to day, due to loan payoffs arising from loan maturity, excess fund or even customers moving to other banks. In this regard, strategies in prospecting new customers, exploring more into the customers potential are needed. Based on the analysis of the survey result employing the descriptive survey method, in order to make sure that the process of identification of prospective customers in Small and Medium Enterprises (SME) segment by Relationship Officers (ROs) running well, focused and appeared to be truly professional in the eye of the customers, then the ROs must be equipped with a set of structured questions and be prepared with interview form in order to progress to the next prospecting steps. Marketing team, i.e. ROs, in understanding and making SME customer or prospective customer priorities, need to classify SME customers or prospective customers into Porcupine, Rabbit, Rhino, Buffalo, so that the feasibility and impact (profitability) from the respected customers or prospective customers can be measured in order to contribute.